2016
DOI: 10.1002/qj.2943
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in winter NAO–wind speed relationships in western Europe linked to concomitant states of the East Atlantic and Scandinavian patterns

Abstract: The 3-hourly gridded ECMWF ERA-Interim climate reanalysis dataset, spanning 1979-2013, was used to investigate the spatial stationarity of the previously documented relationships between wind speeds and the North Atlantic Oscillation (NAO) state in Europe. Over much of western Europe, wind speeds were found to be affected strongly by the concomitant states of the secondary and tertiary atmospheric teleconnections, namely the East Atlantic (EA) and the Scandinavian (SCA) patterns. These modify the geographic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 25 publications
8
71
0
Order By: Relevance
“…Incorporating climate variability into transmission system design (e.g., Kempton et al, 2010) and wind park siting (e.g., Grams et al, 2017) facilitates integration of wind energy. Relevant temporal scales range from subseconds (e.g., Schäfer et al, 2018), over diurnal, synoptic and interannual (e.g., Zubiate et al, 2017), up to multidecadal and centennial timescales (Bett et al, 2017). The last two have received relatively little attention and are therefore the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating climate variability into transmission system design (e.g., Kempton et al, 2010) and wind park siting (e.g., Grams et al, 2017) facilitates integration of wind energy. Relevant temporal scales range from subseconds (e.g., Schäfer et al, 2018), over diurnal, synoptic and interannual (e.g., Zubiate et al, 2017), up to multidecadal and centennial timescales (Bett et al, 2017). The last two have received relatively little attention and are therefore the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…An EA index with reversed polarity has been used in a number of articles (e.g. Wallace and Gutzler, 1981;Comas-Bru and McDermott, 2014;Zubiate et al, 2016), but this does not affect the relationships identified, just the polarity. The third EOF, the Scandinavian pattern (SCA), features high pressure over Scandinavia in its positive phase (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Brayshaw et al , 2011; Clark et al , 2017; Grams et al , 2017; Zubiate et al , 2017) have shown that an important part of the variability of wind electricity generation in Europe on multi‐day time‐scales is governed by the North Atlantic Oscillation (NAO: Wallace and Gutzler, 1981). The NAO is associated with fluctuations in the strength and position of the North Atlantic jet stream.…”
Section: Introductionmentioning
confidence: 99%